The Costs of Being “Different”: Sexual Identity and Subjective Wellbeing over the Life Course - Perales, Francisco; Perales, F (My University, 2016)
Vast social transformations in recent decades have resulted in the emergence of a socio-political climate that is progressively more accepting of sexual minorities. However, sexual identity remains an important aspect influencing people’s lives, and is believed to have independent effects on subjective wellbeing via stigmatization and discrimination of sexual minorities. We use recently available, nationally representative, Australian panel data (n ≈ 15,000 individuals and 111,000 person-year observations) and panel regression models to provide an encompassing and generalizable empirical account of how sexual identity influences a range of subjective wellbeing outcomes, including mental health, life satisfaction, psychological distress and feelings of safety, and how its effects evolve over individuals’ life courses. We find that the subjective wellbeing of gay, lesbian and bisexual individuals is significantly worse than that of heterosexual individuals. Disparities are most apparent during adolescence and early adulthood and tend to close as people age, especially for bisexual individuals. Existing policies outlawing direct discrimination on the grounds of sexual identity in Australia are insufficient and a more global approach to prevent systematic, structural pressures on sexual minorities needed to close sexual identity disparities in subjective wellbeing. Interventions should particularly address the needs of teenagers and young adults.
Keywords: Health -- Wellbeing; Culture; Health and wellbeing; Culture; Health; Wellbeing; Health and wellbeing